Personas for the translational workforce. Issue 4 (10th January 2020) - Gonzales, Sara; O'Keefe, Lisa; Gutzman, Karen; Viger, Guillaume; Wescott, Annie B.; Farrow, Bailey; Heath, Allison P.; Kim, Meen Chul; Taylor, Deanne; Champieux, Robin; Yen, Po-Yin; Holmes, Kristi
Abstract: Twelve evidence-based profiles of roles across the translational workforce and two patients were made available through clinical and translational science (CTS) Personas, a project of the Clinical and Translational Science Awards (CTSA) Program National Center for Data to Health (CD2H). The persona profiles were designed and researched to demonstrate the key responsibilities, motivators, goals, software use, pain points, and professional development needs of those working across the spectrum of translation, from basic science to clinical research to public health. The project's goal was to provide reliable documents that could be used to inform CTSA software development projects, educational resources, and communication initiatives. This paper presents the initiative to create personas for the translational workforce, including the methodology, engagement strategy, and lessons learned. Challenges faced and successes achieved by the project may serve as a roadmap for others searching for best practices in the creation of Persona profiles.